Diseño de un manual de procesos para identificar la exportación del cacao nacional a los Estados Unidos - Calderón Reza, Pamela Lilian (2015)
The present project consisted to make an andragogic and didactic manual of processes to certificate the export of national cocoa to the United States, whose end was to provide the requirements and procedures to the members of the Association “Moradores del Paraíso” from the recinto “Tres Postes”, Guayas province. It should be emphasized that Ecuador is a country highly farm, once of its emblematic products is the national cocoa, fino de aroma, sabor arriba, the same that had conferred many awards worldwide to our country, and continue highlighting to us as one of the higher producers of cacao placing fifthly in the world…..